English Writing Instructional Material for Secondary School Students: A Needs Analysis - Bahjatul Lailah; Amalia, Ila (ELITE JOURNAL, 2025)
This descriptive qualitative study explores the English teaching writing materials needs analysis for secondary students in Indonesia. This study aimed to: (1) analyze the writing teaching materials currently used, (2) identify the specific needs for teaching writing materials, and (3) suggest recommendations for teaching writing materials. The study included 152 secondary school students and one English teacher as the research participants. A questionnaire, interview, and documentation were used as research instruments to collect the data. Findings revealed that the writing teaching materials currently used had met various important aspects of writing skills. The teaching materials were also in accordance with the government curriculum (Merdeka Curriculum) and basic competencies, so that they could help students achieve the expected learning objectives. Furthermore, although the materials used generally aligned with the curriculum and were considered effective, several issues persisted, including limited vocabulary mastery and disparities in students’ writing abilities. The study also revealed that the students required instructional materials that could foster creativity, such as storytelling and article-writing exercises. Based on these findings, some recommendations were proposed, such as providing clearer instructions, incorporating contextualized examples, and developing structured yet creative writing exercises to support student learning.